2021
DOI: 10.3390/plants10020342
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Chloroplast Molecular Markers to Differentiate Sophora toromiro and Its Hybrids as a First Approach to Its Reintroduction in Rapa Nui (Easter Island)

Abstract: Sophora toromiro is an endemic tree of Rapa Nui with religious and cultural relevance that despite being extinct in the wild, still persists in botanical gardens and private collections around the world. The authenticity of some toromiro trees has been questioned because the similarities among hybrid lines leads to misclassification of the species. The conservation program of toromiro has the objective of its reinsertion into Rapa Nui, but it requires the exact genotyping and certification of the selected plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…Generally, the cpSSRs, more easily obtained than the nuclear SSRs, are valuable genetic tools for addressing basic and applied plant biology questions, because of their codominant nature, high polymorphism and low substitution rate. Previous research detected 79 to 135 SSRs and 43 to 56 long repeats in the cpDNAs of six species of genus Euonymus, including E. Japonicus , E. maackii , E. phellomanus , E. schensianus , E. hamiltonianus and E. Fortunei [ 31 ], while the present study detected 282 SSRs and 63 long repeats in the cpDNA of E. microcarpus . Among the SSRs and the long repeats of the seven species of genus Euonymus , the mononucleotide SSRs were the majority, while the complement repeats were the minority.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Generally, the cpSSRs, more easily obtained than the nuclear SSRs, are valuable genetic tools for addressing basic and applied plant biology questions, because of their codominant nature, high polymorphism and low substitution rate. Previous research detected 79 to 135 SSRs and 43 to 56 long repeats in the cpDNAs of six species of genus Euonymus, including E. Japonicus , E. maackii , E. phellomanus , E. schensianus , E. hamiltonianus and E. Fortunei [ 31 ], while the present study detected 282 SSRs and 63 long repeats in the cpDNA of E. microcarpus . Among the SSRs and the long repeats of the seven species of genus Euonymus , the mononucleotide SSRs were the majority, while the complement repeats were the minority.…”
Section: Discussioncontrasting
confidence: 56%
“…Among the SSRs and the long repeats of the seven species of genus Euonymus , the mononucleotide SSRs were the majority, while the complement repeats were the minority. The SSR motifs could serve as potential molecular markers for the species identification, analysis of the population genetic and the genetic differentiation between individuals [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene and intron content are variable relative to most plants ( Guisinger et al, 2011 ). We detected the loss of the trnT-CGU in all mainland’s species compared with two published island species ( S. macrocarpa and S. toromiro ; Pezoa et al, 2021 ). Introns, particularly those located in specific regions, are important for the functionality and regulation of gene expression ( Xu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 78%
“…The repeat sequences may raise the genetic diversity of the species and advance the cpDNA rearrangements [22,39]. Generally, the cpSSRs are valuable genetic tools for population genetics and evolution studies, because of their codominant nature, high polymorphism and low substitution rate [40][41]. The results of the study demonstrated that the genes which have long repeats may be produced as a genetic marker for identifying the related species.…”
Section: Discussionmentioning
confidence: 94%